A camera-based color calibration of tiled display systems under various illumination environments. Issue 2 (3rd April 2017) - Lee, Dong-Hyeok; Yang, Chang-Mo; Park, Yohan; Kim, Choon-Woo
ABSTRACT: Tiled display systems are widely utilized for digital signage application exceeding the size of a single flat-panel display. Smoothly varying spatial non-uniformity in luminance and color may cause visible difference in the boundary of two adjacent sub-displays. It is necessary to suppress such visible artifacts. Tiled display systems can be installed under various illumination environments and require routine color calibration to compensate for temporal change in display characteristics. This paper presents a simple and cost-effective color calibration method for tiled display systems. Consumer-level digital camera is utilized as a measuring device after the proposed vignetting correction was applied. Experimental results indicate that the proposed color calibration method for tiled display system is quite effective in suppressing the visible artifacts across two adjacent sub-displays.